International contacts between Ukraine and Poland in Sports - Кісєль [Jaroslaw Kisiel], Ярослав (Slobozhanskyi Herald of Science and Sport, 2013)
This article presents the development of relations between Ukraine and Poland in one of the disciplines of athletics, namely race walking. Covers the period 1991–2013, i.e. since Ukraine's independence in 1991. Materials for publication are taken from the official reports organizers of sporting events, the newsletter of the International Association of Athletics Federations, book editions. Attention is drawn to the fact that the most powerful training center in Ukraine and Poland in race walking, are located close to each other Ivano-Frankivsk and Mielec. Shows the relationship between the Ukrainian and Polish athletes and their complementarities in the development of race walking in both countries, which contributes to brilliant results in the international arena. Also describes the history of the development of Race Walking events that occurred in Poland and Ukraine.